Effect of Supplementation of Turmeric (Curcuma domestica) in Local Feed-based Goat Rations on in Vitro Digestibility - Susilawati, Susilawati; Syahriani Syahrir; Natsir, Asmuddin; Rahman, Taufica; Hakim, Mita Arifa Hakim (Hasanuddin Journal of Animal Science (HAJAS), 2024)
Turmeric is a widely available herb. This study aimed to determine the effect of Turmeric (Curcume domestica) as an herbal additive in local raw material (LRM) goat rations on dry matter digestibility and organic matter digestibility, pH value, N-ammonia and, in vitro gas production. The study was conducted with a completely randomized design (CRD) of 5 treatments and three replications: treatment T0 = LRM goat ration, T1 = local feed ration (LFR) + turmeric 0.025%, T2 = LFR + turmeric 0.05%, T3 = LFR + turmeric 0.075%, T4 = LFR + turmeric 0.1%. Variance analysis showed that the effect of turmeric (Curcuma domestica) in goat rations made from LRM local has a significant impact (P<0.05) on dry matter digestibility (DMD) and organic matter digestibility (OMD). The most considerable N-ammonia value was obtained in treatment T1, which was 21.13 ± 1.29. From the results obtained, each treatment had a significant effect (P<0.05). The provision of turmeric in goat rations showed promising results regarding the value of rumen N-ammonia. The pH value produced in this study was 6.09 to 7.00, with no significant effect because the pH in the rumen has been maintained. Keywords: Feed additive, turmeric, pH, N-ammonia, in vitro